FACTORS THAT DRIVE E-COMMERCE ADOPTION IN UMKM - Nasruddin (CV Naskah Aceh, 2024)
This research aims to identify the factors that influence the decision of footwear MSMEs in Cibaduyut to adopt e-commerce. Using the Theory of Planned Behavior (TPB) as the main theoretical framework, this research also considers the Technology-Organizational-Environmental (TOE) model to understand technological, organizational and environmental factors as well as personal factors of MSME owners. Primary data was collected through questionnaires filled out by 148 respondents from footwear MSMEs in Cibaduyut, and analyzed using the multiple linear regression method. The research results show that MSMEs have a positive attitude towards e-commerce, influenced by social norms, perceived behavioral control, perceived benefits, and government support. These findings suggest that MSMEs that have not yet adopted e-commerce need to consider the potential benefits, while those that have adopted can evaluate the existing challenges. The government is expected to contribute through training, infrastructure and regulations that support the use of e-commerce in MSMEs.